Blood Bacterial Profiles Associated With Human Immunodeficiency Virus Infection and Immune Recovery. (30th June 2020) - Serrano-Villar, Sergio; Sanchez-Carrillo, Sergio; Talavera-Rodríguez, Alba; Lelouvier, Benjamin; Gutiérrez, Carolina; Vallejo, Alejandro; Servant, Florence; Bernadino, José I; Estrada, Vicente; Madrid, Nadia; Gosalbes, María José; Bisbal, Otilia; et al.
Abstract: Human immunodeficiency virus (HIV) infection impairs mucosal immunity and leads to bacterial translocation, fueling chronic inflammation and disease progression. While this is well established, questions remain about the compositional profile of the translocated bacteria, and to what extent it is influenced by antiretroviral therapy (ART). Using 16S ribosomal DNA targeted sequencing and shotgun proteomics, we showed that HIV increases bacterial translocation from the gut to the blood. HIV increased alpha diversity in the blood, which was dominated by aerobic bacteria belonging to Micrococcaceae (Actinobacteria) and Pseudomonadaceae (Proteobacteria) families, and the number of circulating bacterial proteins was also increased. Forty-eight weeks of ART attenuated this phenomenon. We found that enrichment with Lactobacillales order, and depletion of Actinobacteria class and Moraxellaceae and Corynebacteriacae families, were significantly associated with greater immune recovery and correlated with several inflammatory markers. Our findings suggest that the molecular cross talk between the host and the translocated bacterial products could influence ART-mediated immune recovery. Abstract : In this longitudinal study in human immunodeficiency virus (HIV)–infected individuals, we found a specific signature of bacterial circulating DNA sequences and proteins, suggesting that molecular cross talk between host and translocated bacterial products could influence antiretroviral therapy–mediated immune recovery.